Odontogenic infections and therapeutic management in patients treated at the Hipólito Unanue National Hospital - Angeles Chumbiriza, Medaliht (2022)
Objective: To determine the diagnosis and therapeutic management of odontogenic infections in patients treated in a Peruvian hospital. Materials and methods: The study was descriptive, retrospective and cross-sectional, non-probabilistic sampling for convenience. A total of 4968 operative reports were collected, from which 142 medical records that met the inclusion criteria were reviewed: medical records of patients who received treatment in the oral and maxillofacial surgery service of the Hipólito Unanue National Hospital (HNHU), and who had a diagnosis of odontogenic infection. The exclusion criteria were: medical records with incomplete information, with diagnoses of infections of non-odontogenic origin, with a diagnosis of dentoalveolar or facial trauma. Results: Of the total medical records that are part of the investigation, the age was most frequently between 26 and 44 years and 58.45% were female. The most prevalent diagnosis was abscess (60.56%) and cellulitis (26.76%). The most frequently used surgical procedure was drainage/extraction (33.80%) followed by extraction (27.46%). Regarding the pharmacological treatment, the most used was the bactericide (61.97%). Conclusions: It is concluded that the most prevalent diagnosis was abscess and cellulitis.